A note on observational equivalence of micro assumptions on macro level - Alexey Ponomarenko (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The author set up a simplistic agent-based model where agents learn with reinforcement observing an incomplete set of variables. The model is employed to generate an artificial dataset that is used to estimate standard macro econometric models. The author shows that the results are qualitatively indistinguishable (in terms of the signs and significances of the coefficients and impulse-responses) from the results obtained with a dataset that emerges in a genuinely rational system.
http://dx.doi.org/10.7910/DVN/MWELOD
Keywords: B41; C63; D83; 330; microfoundations; bounded rationality; reinforcement learning; agent- based model